Moral and Science Integration in The Qur’anic Education Perspective - Asy'ari, Muhammad (LPPM IAIN Kudus, 2018)
Education is a very important factor for humans, because it can determine the progress of a nation. Man is not only directed to the increase of knowledge, but also moral or morals. In the concept of Islam, education and teaching must be integrated between science and morals. The approach used by the Qur’an in educating and teaching humanity is to achieve balance and harmony symbolized by hasanah fi ad-dunya wa hasanah fi al-akhirah. After man sincerely worship him, then burdened with education and teaching related to educating, teaching and guiding his soul, such as obeying parents, respect for the elder, love the younger and so forth. It is intended by the Qur’an that man is always holy and keep the holiness that God gives. While the power of human thought is directed to read and analyze and conclude the signs and signs of God’s greatness. In such circumstances the Qur’an will be able to give direction, educate and teach people to the path of ultimate life happiness.